Ghana eTrade Readiness Assessment - United Nations Conference on Trade; Development (United Nations, 2023)
The eTrade Readiness Assessment of Ghana expands UNCTADs ongoing e-commerce technical assistance in West Africa, in alignment with the ECOWAS E-Commerce Strategy adopted in July 2023. Building on eight national assessments and two regional assessments, for the West African Economic Monetary Union and the Economic Community of West African States, this assessment details the challenges and policy gaps prevalent within Ghana's burgeoning e-commerce sector as well as Ghana's potential to harness national initiatives and government-backed projects to foster the growth of the digital economy. The policy recommendations outlined in Ghana's eT Ready report are strategically tailored to foster a more inclusive and sustainable development trajectory. They are designed to support Ghana's Industrial Transformation Programme and Digitalization Agenda, aligning with ongoing efforts by ECOWAS members to advance e-commerce within the region through the ECOWAS E-commerce Strategy.